THE EFFECT OF BUILDING THE ISLAMIC CHARACTER OF STUDENTS AT WISMA PADANG STATE UNIVERSITY - Efendi, Efendi; Ramadhani, Ramadhani; Kamil, Rheschy Auliya; Rahman, Ikhwan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to describe the process of forming the Islamic character of students at Wisma Padang State University. This study uses a qualitative method with a case study design approach, the research data is taken using a set of interview protocols that the author made and has been validated by one methodology expert to ten informants (students), the informants were selected using a purposive sampling technique. All interview results were then analyzed thematically using. Overall, the research findings found that there were five character changes in students after living at Wisma Padang State University. The five findings are; i) dress according to syar'i, ii) higher learning motivation, iii) polite and courteous to fellow friends, iv) more efficient in managing finances, v) make good use of time. The results of this study can be used as initial data for future researchers in examining this problem in different contexts and issues